Rebel Daughters : Women and the French Revolution. - Melzer, Sara E. (Oxford University Press, 1993)
This interdisciplinary collection of essays examines the important and paradoxical relation between women and the French Revolution. Although the male leaders of the Revolution depended on women's active militant participation, they denied to women the rights that women helped to establish.